2020
DOI: 10.7759/cureus.9695
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gastrografin in Patients With Small Bowel Obstruction

Abstract: Introduction Gastrografin (GGF) is a radiopaque contrast medium commonly used for diagnostic examination of the gastrointestinal (GI) tract. Available evidence suggests it has therapeutic and predictive value in the management of adhesional small bowel obstruction (ASBO). Thus, we investigated the use of GGF amongst patients who had a small bowel obstruction and audited the practice in University Hospital, Ayr. Methods Initial retrospective data of patients who had gastrografin for small bowel obstruction were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 10 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…From our study, more than 81% of cases of ABO resolved with gastrogra n administration demonstrating a signi cant bene t in conservative management of ABO. This bene t is supported by evidence from randomized controlled trials that detailed further bene ts, as providing expedited resolution of obstruction, allowing earlier discharge and reducing the need for surgery in some patients [17,18].…”
Section: Discussionmentioning
confidence: 94%
“…From our study, more than 81% of cases of ABO resolved with gastrogra n administration demonstrating a signi cant bene t in conservative management of ABO. This bene t is supported by evidence from randomized controlled trials that detailed further bene ts, as providing expedited resolution of obstruction, allowing earlier discharge and reducing the need for surgery in some patients [17,18].…”
Section: Discussionmentioning
confidence: 94%
“…In nonemergent SBOs, non-operative/conservative management is promptly initiated. Conservative management options, dependent on the patient's well-being, include fluid resuscitation, pain control, restricting oral intake, antibiotics, and NG tube placement [11,12]. The aforementioned non-operative management can resolve certain types of SBOs, the sequelae being bowel decompression.…”
Section: Discussionmentioning
confidence: 99%
“…Failed conservative management and a high pretest probability of bowel compromise (bowel ischemia, necrosis, or perforation) upon clinical or radiographic examination should bypass non-operative management and the patient be taken immediately for surgical intervention [12]. A patient with complete bowel obstruction is at increased risk of life-threatening complications due to bowel ischemia and perforation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study in 2020 also concluded that gastrografin has a major therapeutic role in relieving adhesive small intestinal obstruction and refractory constipation. Compared to a CT scan, it is more effective and has a higher diagnostic value (82.5% vs 92.3%) [16]. The UK national audit recommends the use of gastrografin after 48 hours of conservative treatment and operative treatment after 24 hours of gastrografin administration and no improvement [17].…”
Section: Discussionmentioning
confidence: 99%